Insights on the Role of Mesenchymal Stromal Cells Infusion in Enhancing the Inhibitory Network and Synaptic Plasticity in Chronic Epileptic Rats - Rania S. Salah (Journal of Global Pharma Technology, 2016)
Objective: Temporal lobe epilepsy (TLE) is characterized by progressive synchronization with high frequencies of drug resistance. Mesenchymal stromal cells (MSCs) could open promising avenues for epileptic therapeutic approaches. The rational of the current research was to realize the therapeutic outcome of bone marrow (BMSCs) and adipose (ADMSCs)-drived MSCs against chronic epileptogenic alterations implicated in pilocarpine-induced TLE. Methods: Adult male Wister rats were distributed into five groups: Gp1: non epileptic control group, Gp2: chronic epileptic control group, Gp3: chronic epileptic group treated with BMSCs, Gp4: chronic epileptic group treated with ADMSCs and Gp5: chronic epileptic group treated with carbamazepine (CBZ). Gama-aminobutyric acid (GABA), semaphorin4D (Sema4D) and galanin concentrations were evaluated in brain via ELISA. Gene expression level of hippocampal synapsin-I was estimated using sqRT-PCR. Histological explorations of hippocampus and cerebral cortex were carried out. Results: Significant decline in GABA, galanin and Sema4D contents as well as synapsin-I mRNA level were recorded after pilocarpine injection. BMSCs or ADMSCs transplantation or CBZ administration constructed significant upgrade in GABA, galanin and Sema4D concentrations as well as synapsin-I mRNA level. Micrograph of brain tissue sections of epileptic rats showed nucleus pyknosis and neurodegeneration while, the treated groups demonstrated almost intact histological architecture. Conclusion: Based on the forementioned results, this work established the exact mechanisms underlining epileptogenesis and offered a new hope for treatment of focal epilepsies by employment of MSCs which achieved significant neuroprotective activity through modulating epileptic neuronal circuit, secreating neurotrophic molecules and restoring synaptic plasticity. Keywords: Chronic epilepsy, mesenchymal stromal cells, neuroprotection, GABA, Sema4D, galanin, synapsin-I.